Discover the answers you need at Westonci.ca, a dynamic Q&A platform where knowledge is shared freely by a community of experts. Get detailed and accurate answers to your questions from a community of experts on our comprehensive Q&A platform. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.
Sagot :
To solve the equation given as the determinant of a 3x3 matrix equal to zero, we will proceed by calculating the determinant of the matrix. The matrix in question is:
[tex]\[ \begin{pmatrix} 3 & 4 & -1 \\ 2 & 0 & 7 \\ 1 & -3 & -2 \end{pmatrix} \][/tex]
To find the determinant of a 3x3 matrix, we use the standard formula:
[tex]\[ \text{det}(A) = a(ei - fh) - b(di - fg) + c(dh - eg) \][/tex]
where
[tex]\[ A = \begin{pmatrix} a & b & c \\ d & e & f \\ g & h & i \end{pmatrix} \][/tex]
For the given matrix:
[tex]\[ \begin{pmatrix} 3 & 4 & -1 \\ 2 & 0 & 7 \\ 1 & -3 & -2 \end{pmatrix} \][/tex]
We can assign the values as follows:
[tex]\[ a = 3, \; b = 4, \; c = -1, \; d = 2, \; e = 0, \; f = 7, \; g = 1, \; h = -3, \; i = -2 \][/tex]
Substituting these values into the formula:
[tex]\[ \text{det}(A) = 3((0 \cdot -2) - (7 \cdot -3)) - 4((2 \cdot -2) - (7 \cdot 1)) + (-1)((2 \cdot -3) - (0 \cdot 1)) \][/tex]
Now calculate each term individually:
1. Calculate [tex]\(3((0 \cdot -2) - (7 \cdot -3))\)[/tex]:
[tex]\[ 3(0 + 21) = 3 \cdot 21 = 63 \][/tex]
2. Calculate [tex]\(-4((2 \cdot -2) - (7 \cdot 1))\)[/tex]:
[tex]\[ -4(-4 - 7) = -4(-11) = 44 \][/tex]
3. Calculate [tex]\((-1)((2 \cdot -3) - (0 \cdot 1))\)[/tex]:
[tex]\[ -1(-6 - 0) = -1(-6) = 6 \][/tex]
Sum these results:
[tex]\[ \text{det}(A) = 63 + 44 + 6 = 113 \][/tex]
Thus, the determinant of the matrix is 113. Given that the determinant is not equal to zero, the original equation should be interpreted based on correct determinant properties. The determinant of the given matrix is indeed 113.
[tex]\[ \begin{pmatrix} 3 & 4 & -1 \\ 2 & 0 & 7 \\ 1 & -3 & -2 \end{pmatrix} \][/tex]
To find the determinant of a 3x3 matrix, we use the standard formula:
[tex]\[ \text{det}(A) = a(ei - fh) - b(di - fg) + c(dh - eg) \][/tex]
where
[tex]\[ A = \begin{pmatrix} a & b & c \\ d & e & f \\ g & h & i \end{pmatrix} \][/tex]
For the given matrix:
[tex]\[ \begin{pmatrix} 3 & 4 & -1 \\ 2 & 0 & 7 \\ 1 & -3 & -2 \end{pmatrix} \][/tex]
We can assign the values as follows:
[tex]\[ a = 3, \; b = 4, \; c = -1, \; d = 2, \; e = 0, \; f = 7, \; g = 1, \; h = -3, \; i = -2 \][/tex]
Substituting these values into the formula:
[tex]\[ \text{det}(A) = 3((0 \cdot -2) - (7 \cdot -3)) - 4((2 \cdot -2) - (7 \cdot 1)) + (-1)((2 \cdot -3) - (0 \cdot 1)) \][/tex]
Now calculate each term individually:
1. Calculate [tex]\(3((0 \cdot -2) - (7 \cdot -3))\)[/tex]:
[tex]\[ 3(0 + 21) = 3 \cdot 21 = 63 \][/tex]
2. Calculate [tex]\(-4((2 \cdot -2) - (7 \cdot 1))\)[/tex]:
[tex]\[ -4(-4 - 7) = -4(-11) = 44 \][/tex]
3. Calculate [tex]\((-1)((2 \cdot -3) - (0 \cdot 1))\)[/tex]:
[tex]\[ -1(-6 - 0) = -1(-6) = 6 \][/tex]
Sum these results:
[tex]\[ \text{det}(A) = 63 + 44 + 6 = 113 \][/tex]
Thus, the determinant of the matrix is 113. Given that the determinant is not equal to zero, the original equation should be interpreted based on correct determinant properties. The determinant of the given matrix is indeed 113.
We hope this information was helpful. Feel free to return anytime for more answers to your questions and concerns. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Thank you for using Westonci.ca. Come back for more in-depth answers to all your queries.